2017
DOI: 10.1371/journal.pone.0174956
|View full text |Cite
|
Sign up to set email alerts
|

Maltose binding protein-fusion enhances the bioactivity of truncated forms of pig myostatin propeptide produced in E. coli

Abstract: Myostatin (MSTN) is a potent negative regulator of skeletal muscle growth. MSTN propeptide (MSTNpro) inhibits MSTN binding to its receptor through complex formation with MSTN, implying that MSTNpro can be a useful agent to improve skeletal muscle growth in meat-producing animals. Four different truncated forms of pig MSTNpro containing N-terminal maltose binding protein (MBP) as a fusion partner were expressed in E. coli, and purified by the combination of affinity chromatography and gel filtration. The MSTN-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have shown that synthetic peptides containing 29 or 24 amino acids from the mouse MSTNpro were sufficient to suppress MSTN activity in vitro and to increase muscle mass in mice of muscular dystrophy model [12, 13]. We also have shown that truncated forms of pig and flatfish MSTNpro with an N-terminal fusion of maltose binding protein (MBP) had the MSTN-inhibitory capacity not different from the full sequence mouse MSTNpro [35, 36]. Notably, the size of MSTNpro region of flatfish (residues 45–80) was much smaller than that of pig (residues 42–175) for full MSTN-inhibitory capacity, suggesting that the large sequence variation between fish and mammalian MSTNpro affects the stability of MSTNpro and MSTN complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that synthetic peptides containing 29 or 24 amino acids from the mouse MSTNpro were sufficient to suppress MSTN activity in vitro and to increase muscle mass in mice of muscular dystrophy model [12, 13]. We also have shown that truncated forms of pig and flatfish MSTNpro with an N-terminal fusion of maltose binding protein (MBP) had the MSTN-inhibitory capacity not different from the full sequence mouse MSTNpro [35, 36]. Notably, the size of MSTNpro region of flatfish (residues 45–80) was much smaller than that of pig (residues 42–175) for full MSTN-inhibitory capacity, suggesting that the large sequence variation between fish and mammalian MSTNpro affects the stability of MSTNpro and MSTN complex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intramuscular injection of the truncated MSTNpro peptides increased muscle mass in Duchenne and caveolin 3-deficient limb-girdle muscular dystrophy model mice [12, 13]. In our study, maltose binding protein (MBP)-fused pig MSTNpro region containing residues 42–175 exhibited full MSTN-inhibitory potency [35]. Similarly, flatfish MSTNpro region containing residues 45–80 showed MSTN-inhibitory potency comparable to that of full sequence mouse MSTNpro [36], indicating that MBP fused, truncated MSTNpro peptides would be potential agents to treat muscle wasting conditions.…”
Section: Introductionmentioning
confidence: 94%
“…According to the preliminary analysis of physicochemical parameters, the ORF55 protein was unstable and not highly hydrophilic (Table 1 ), indicating that the final purified protein may not be highly soluble and/or easily degraded. Based on these analyses, the pMAL-c5X vector was selected for gene cloning because MBP is known to be highly soluble [ 41 ] and can enhance the biological activity of fused target proteins [ 42 ]. We successfully cloned the ORF55 gene into the pMAL-c5X vector, and expressed and purified the MBP-ORF55 fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that there were no significant differences in gene expression and amino acid sequences of myostatin between fastand slow-growing groups of chickens. Allegedly, the physiological function of myostatin in not only affected by the myostatin gene expression but also affected by other molecules, i.e TGF-β1 (Zhu et al 2007), decorin (Zhu et al 2007), follistatin and follistatin associated genes (Lee and McPherron 2001), myostatin propeptide (Haq et al 2013;Lee et al 2016Lee et al , 2017, Bone Morphogenetic Protein-1 (Lee 2010), Tolloid (Lee 2010), and Tolloid-like-1 and 2 (Lee 2010).…”
Section: Myostatin Mrna Expressionmentioning
confidence: 99%